2020
DOI: 10.3389/fnins.2020.585432
|View full text |Cite
|
Sign up to set email alerts
|

microRNA-Based Biomarkers in Alzheimer’s Disease (AD)

Abstract: Alzheimer's disease (AD) is a multifactorial, age-related neurological disease characterized by complex pathophysiological dynamics taking place at multiple biological levels, including molecular, genetic, epigenetic, cellular and large-scale brain networks. These alterations account for multiple pathophysiological mechanisms such as brain protein accumulation, neuroinflammatory/neuro-immune processes, synaptic dysfunction, and neurodegeneration that eventually lead to cognitive and behavioral decline. Alterat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
69
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 64 publications
(70 citation statements)
references
References 167 publications
0
69
0
1
Order By: Relevance
“…Progressive, low-grade, systemic inflammation and inflammatory neurodegeneration is known to be linked with a complicated network of miRNAs and their target mRNAs, out of which some miRNAs play a promoting role [ 49 ]. In contrast, the miR-483-5p activity reported here seems to represent neuroprotective/compensatory mechanisms in AD.…”
Section: Discussionmentioning
confidence: 99%
“…Progressive, low-grade, systemic inflammation and inflammatory neurodegeneration is known to be linked with a complicated network of miRNAs and their target mRNAs, out of which some miRNAs play a promoting role [ 49 ]. In contrast, the miR-483-5p activity reported here seems to represent neuroprotective/compensatory mechanisms in AD.…”
Section: Discussionmentioning
confidence: 99%
“…In similar studies analyzing the influence of the confounding factors age and sex on miRNA profiles from peripheral blood, it was found that very few single miR-NAs remained significantly associated with age and sex after adjustment using multiple testing parameters 44 . This lack of significant association may also be a reflection of (I) the observation that many miRNA biomarkers show discrepant results in independent investigations of the same disease, and (II) the remarkable heterogeneity of miRNA complexity and expression patterns in neurological disorders, such as those observed across the entire AD continuum 45 . We report significantly lower levels of miRNA-15b in Aβ-positive individuals than -negative ones.…”
Section: Discussionmentioning
confidence: 99%
“…The miR-34 and miR-122 miRNAs have been used in the treatment of certain types of cancer and hepatitis, with promising results [ 64 ]. On the other hand, some miRNAs (miRNA-9, miRNA-34a, miRNA-125b, miRNA-146a, and miRNA-155) may be involved in the physiopathology of AD, and some act on the Wnt/β-catenin pathway [ 65 ], which is involved in both neurodegenerative diseases and tumors. A recent paper suggested a potential anti-β-amyloid protective effect of miRNA-15b and a biological link between miRNA-125b and neurotoxic pathways, hypothesizing that these miRNAs may play a role as biomarkers of AD physiopathology with therapeutic potential [ 66 ].…”
Section: Cancer and Neurodegenerative Diseasesmentioning
confidence: 99%